Unconventional Protein Secretion Dependent on Two Extracellular Vesicles: Exosomes and Ectosomes - Meldolesi, Jacopo (Frontiers in Cell and Developmental Biology, 2022)
In addition to its conventional form, dependent on specific signal sequences, protein secretion occurs by other forms widely called unconventional, dependent on several mechanisms. Among the cell organelles of the latter forms of secretion are two families of vesicle, generated and employed by all types of cells, the exosomes and ectosomes, with average diameters of ∼70 and ∼250 nm. As long as intracellular, the two types of vesicles are distinct. Exosomes, developed by peculiar microdomains of cargos from the cytosol and of membrane from endocytic vacuoles, accumulate within the latter called multivesicular bodies (MVB). In addition to their interaction with lysosomes and autophagosomes, MVBs respond to signaling stimulation by surface exocytoses, with ensuing extracellular diffusion of exoxomes. Ectosomes develop, however rapidly, in response to analogous signaling stimulation, by employment of microdomains from the plasma membrane and distinct cytosolic cargos. Upon shedding they are directly released. In the extracellular fluid both vesicles differ from conventional secreted materials composed by only molecules. The unconventional vesicles maintain their membranes, are very resistant, navigate for various times and various distances until their interaction to cells specific for their fusion, with discharge of cargoes into their cytoplasm. Secretion/navigation/fusion of vesicles generated by all cells establishes continuous tridimensional networks exchanging molecules, signals and information among cells. Identified proteins of unconventional secretion, devoid of conventional signal sequence, are several hundreds. Some of them are functionally relevant, governing physiological processes and several important diseases. Relevance of these proteins and their function, at present intensely investigated, predict important future discoveries and innovative developments, relevant from basic research to clinical practice.